Sanctionable Behavior in a Felony Level Drug Court: Categorizing Noncompliant Behavior Through a Criminal-Thinking Lens - Bonomo, Elizabeth (2012)
Drug courts use sanctions as a form of behavior management and modification, and they are an important structural tool in the treatment of drug offenders by the criminal justice system. This research examined noncompliant behavior being sanctioned in a felony level drug court. The sample consisted of 66 high risk/high needs individuals who were enrolled in a drug court over a two-year period. Sanctionable behaviors were analyzed through a criminal-thinking framework in order to better understand noncompliant behavior in drug court. This study finds support for applying a criminal-thinking framework to noncompliant behavior sanctioned in drug court. The findings from this study illustrate the nuances of noncompliant behavior of a drug court population